Stiffness Design of Unbraced Steel Frames - Cheong-Siat-Moy, F. (Engineering Journal, 1976)
In considering the serviceability of unbraced multistory steel buildings at working loads, the ability of the bents to limit lateral deflections is of prime importance. The parameter most commonly used in the measurement of their stiffnesses is the frame drift index, which is defined as the sway recorded at the uppermost level of a frame divided by its total height. To control cracking in light partitions and in windows, the frame drift index is not an appropriate criteria to use. A more suitable indicator would be the story drift index, which is the ratio of the relative sway of a story to its height. This is so because story deflections are non-uniform and generally vary markedly throughout the frames height. In most conventional frames, improving beam inertias will efficiently reduce lateral sway; however, in some cases it is more desirable to increase column sizes and beam sizes simultaneously. This paper provides simple guidelines in deciding which course of action to take. The method is simple, fast, direct, and suitable for dealing with first-order as well as second-order deflections.